2000
DOI: 10.1080/00150190008016036
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional ferroelectrics

Abstract: Blinov, L. M.; Fridkin, V. M.; Palto, S.P.; Bune, A. V.; Dowben, Peter A.; and Ducharme, Stephen, "Two-Dimensional Ferroelectrics" (2000). Abstract. The investigation of the finite-size effect in ferroelectric crystals and films has been limited by the experimental conditions. The smallest demonstrated ferroelectric crystals had a diameter of $ 200 A and the thinnest ferroelectric films were $ 200 A thick, macroscopic sizes on an atomic scale. Langmuir ± Blodgett deposition of films one monolayer at a time ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Furthermore, this first-order ferroelectric phase transition is almost independent of the film thickness in crystalline copolymer films, indicating the existence of two-dimensional ferroelectricity. 24,26,[35][36][37] A first-order surface ferroelectric phase transition was also observed at T C S =20°C, 25,29,31,36,37 attributed to the dimensionality effect associated with the lower coordination at the surface. 25,29 The spatial dimension of polarization control in thin films of P(VDF-TrFE) has decreased substantially in the past decade.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Furthermore, this first-order ferroelectric phase transition is almost independent of the film thickness in crystalline copolymer films, indicating the existence of two-dimensional ferroelectricity. 24,26,[35][36][37] A first-order surface ferroelectric phase transition was also observed at T C S =20°C, 25,29,31,36,37 attributed to the dimensionality effect associated with the lower coordination at the surface. 25,29 The spatial dimension of polarization control in thin films of P(VDF-TrFE) has decreased substantially in the past decade.…”
Section: Introductionmentioning
confidence: 86%
“…Local external electronic fields can affect the orientation of the monomer dipole moments of P(VDF-TrFE) films, 11,22,30,[35][36][37][38][39][40][41] thus resulting in local polarization and local switching (dipole reversal). 30 In previous experiments, the polarization alignment and conductance switching were achieved by changing the value and the polarity of the tipbias voltage.…”
Section: Stm-induced Structural Distortionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, experiment has shown that ferroelectricity can still exist in the film of a few nanometers thick. 8 Thus, the assumption of a nonferroelectric interfacial is problematic. In our previous work, 9 instead of assuming a nonferroelectric layer, we proposed that this layer is still ferroelectric with parameters different from those of the interior region.…”
Section: Introductionmentioning
confidence: 99%